2021
DOI: 10.1177/23800844211057793
|View full text |Cite
|
Sign up to set email alerts
|

Age of First Oral Health Examination and Dental Treatment Needs of Medicaid-Enrolled Children

Abstract: Introduction: Early childhood caries (ECC), despite being preventable, remains the most prevalent disease of childhood, particularly in children between the ages of 2 and 5 y. The association between the type of health care provider completing initial oral health examinations and subsequent dental caries in children under 6 y of age is unclear. Objective: The objective of the current study is to longitudinally assess the association between age at first oral health examination and provider type at first oral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Given that preterm infants with a lower GA often have sequelae of prematurity, such as brain disorders [25][26][27], lung disorders [28-30], and lack of motor skills [31,32], they are more likely to receive periodic check-ups and treatments at general hospitals. Compared with physicians and general dentists, pediatric dentists are not only more knowledgeable about oral development and issues in infants and toddlers than general dentists or physicians [33,34], but they also provide more proactive interventions and a higher level of expertise in addressing oral problems [35]. Therefore, there is a higher likelihood of doctors assessing oral health issues early and referring comprehensive oral examinations to pediatric dentists at the same or nearby general hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Given that preterm infants with a lower GA often have sequelae of prematurity, such as brain disorders [25][26][27], lung disorders [28-30], and lack of motor skills [31,32], they are more likely to receive periodic check-ups and treatments at general hospitals. Compared with physicians and general dentists, pediatric dentists are not only more knowledgeable about oral development and issues in infants and toddlers than general dentists or physicians [33,34], but they also provide more proactive interventions and a higher level of expertise in addressing oral problems [35]. Therefore, there is a higher likelihood of doctors assessing oral health issues early and referring comprehensive oral examinations to pediatric dentists at the same or nearby general hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This issue could be due to inadequately trained dental providers who are comfortable managing special-needs children and compounded by difficulty in locating dental offices that accept government funded insurance due to substantially lower reimbursement fees versus private dental insurances. 6,7,10,22,23 A recent study reported that in California 5% of dentists in suburban areas and 3% in rural areas participated in Medicaid program. 24 Only 11% of pediatric dentists in California participated in state's Medicaid program, which is one of the lowest in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistical difference between the groups. Literature showed that caries risk for children enrolled in Medicaid insurance when their first dental exams were at 4 years old is 5 times higher than those whose dental exams were before the age 1 21,22 . Hence, more awareness is needed so that children could be seen for their first dental exam by age 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is no surprise that many of the reports in this January 2023 issue focus on 2 of the most vulnerable populations worldwide for poor oral health: children and older adults. Ahmed et al (2021) describe a quantitative analysis of almost 2.5 million children enrolled in the US Medicaid system. Consistent with previous published literature, their analysis indicates that children who have their first dental visit at the age of 4 y have significantly higher hazard ratios for dental caries (more than 5 times greater) than children who have their first dental visits at the age of 1 y.…”
mentioning
confidence: 99%